2012
DOI: 10.1007/s11999-012-2377-5
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Developing Countries in Orthopaedic Journals: A Survey of Four Influential Orthopaedic Journals

Abstract: Background The developing world contains more than of the world's population, and has the largest burden of musculoskeletal disease. Published studies provide crucial information that can influence healthcare policies. Presumably much information regarding burden in the developing world would arise from authors from developing countries. However, the extent of participation of authors from the developing world in widely read orthopaedic journals is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 20 publications
1
37
1
Order By: Relevance
“…Despite the strain of increasing incidence globally of musculoskeletal disease, there is a paucity of clinical research in orthopaedic surgery emerging from developing countries [2,38]. Research originating in developing countries is necessary to address questions that are of importance specifically to low-resource settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the strain of increasing incidence globally of musculoskeletal disease, there is a paucity of clinical research in orthopaedic surgery emerging from developing countries [2,38]. Research originating in developing countries is necessary to address questions that are of importance specifically to low-resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…This skewed resource allocation is particularly pronounced in the orthopaedic literature where increased global musculoskeletal disease and trauma in the developing world have not been met with a concomitant increase in attention or funding [2,17,30]. Research is a way to contribute lasting change in a lowresource setting and is as important as research performed in a high-resource setting.…”
Section: Introductionmentioning
confidence: 99%
“…8 Aluede et al believes that multinational and cross-institutional collaborations and the initiation of educational programmes will generate more studies. 5 The most important step might be the implementation of a mentoring programme. However, the lack of willingness of senior scientists and surgeons, and the lack of protected time are major limitations that must be addressed for this to be successful.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of willingness of senior scientists and surgeons, and the lack of protected time are major limitations that must be addressed for this to be successful. 5,21,22 Bennett et al have suggested that mentoring could also be achieved by training mentors in the developed world. 24 Finally the SA Orthopaedic Journal should be encouraged to apply to be indexed on Medline for worldwide dissemination of African-based research.…”
Section: Discussionmentioning
confidence: 99%
“…Without such data, one can only speculate as to whether adverse clinical outcomes might be related to suboptimal mechanical characteristics of the type observed. Considerable difficulties exist in performing clinical studies in low-income countries to answer such questions, given both the lack of research funding and the challenges in publishing such studies in high-impact orthopaedic journals [17].…”
Section: Discussionmentioning
confidence: 99%